Redesain Kemasan Keripik Tempe Menggunakan Metode Quality Function Deployment dan Value Engineering - Ernawati, Siti; Muhammad, Katon; Asyari, Hasyim (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2024)
The existing Gandhes tempeh chips packaging is not air- and water-tight so it is at risk of damage such as not crispy, easily destroyed, and rancid odor. These packaging problems require packaging development in order to improve the function of the packaging. The purpose of this study is to determine packaging attributes based on consumer preferences to increase the value of Ghandes tempeh chips packaging based on the highest value. Improvement is done by integrating Quality Function Deployment and Value engineering techniques with the help of House of Quality, FAST diagram, and concept combination table. Quality Function Deployment method to identify customer needs by finding weights and technical responses, while Value engineering to analyze packaging functions needed by consumers and recommend the best packaging based on the highest value. The results are 10 attributes that become consumer needs (whats) and 12 technical responses (hows). The results showed 4 alternative packaging concepts that can be made and sorted to determine the best concept in terms of cost and performance. The selected alternative concept is Alternative C with a score of 1.78. The selected packaging specifications include 100 micron metalized paper material, information label, matte finishing, standing pouch, size 17×29 cm, weight 200 grams, ziplock packaging, price per package Rp 2,850, using a combination of red and orange colors. It can be concluded that this proposal is the best proposal in terms of the highest value. This recommendation can be considered capable of fulfilling consumer desires for Gandhes tempeh chips packaging.